PERAN BAWASLU DALAM MENCEGAH PRAKTIK POLITIK UANG PADA PEMILIHAN KEPALA DAERAH TAHUN 2024 DI KABUPATEN KEPULAUAN TAMIMBAR - Rosario Bembuain; Polikarpus Lalamafu; Aresyama Hein Temmar; Amtai Alaslan (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
Money politics, referred to as "the mother of corruption," is a major and frequent problem in Indonesia’s direct leadership succession processes. Voter choice is not merely a procedure; the electoral process is an important instrument to correct, assess, evaluate, and improve the administration of government. If vote-buying is allowed to continue, its impact can be significant and even harm the state or regions. Candidates who win through vote-buying have the potential to maintain power in an unhealthy manner. This study aims to analyze the role of the Election Supervisory Agency (Bawaslu) of Tanimbar Islands Regency in efforts to prevent vote-buying during the 2024 Regional Head Election. The research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. Findings indicate that Bawaslu implemented various preventive strategies, such as public outreach, vulnerability mapping, and anti–vote-buying patrols. However, several constraints were identified, including limited human resources, difficult and remote geographic conditions, and a local political culture that remains tolerant of vote-buying transactions. This study recommends increasing community participation, utilizing technology in oversight activities, and strengthening cross-institutional collaboration to make efforts to prevent vote-buying more effective.